Nasal carriage rate of methicillin resistant Staphylococcus aureus among Iranian healthcare workers: a systematic review and meta-analysis - Emaneini,Mohammad (2017)
Abstract Globally, methicillin-resistant Staphylococcus aureus (MRSA) remains a major cause of healthcare-associated infections. Healthcare workers (HCWs), patients and the environment may act as reservoirs for the spread of MRSA to patients and other HCWs. Screening and eradication of MRSA colonization is an effective method of reducing the MRSA infection rate. There are limited data on the prevalence of MRSA among Iranian HCWs. We performed a systematic search by using different electronic databases including Medline (via PubMed), Embase, Web of Science, and Iranian Databases (from January 2000 to July 2016). Meta-analysis was performed using the Comprehensive Meta-Analysis (Biostat V2.2) software. The meta-analyses showed that the prevalence of S. aureus and MRSA among HCWs were 22.7% [95% confidence interval (CI): 19.3-26.6] and 32.8% (95% CI: 26.0-40.4) respectively. The high rate of nasal MRSA carriage among Iranian HCWs has been attributed to poor compliance to hand hygiene, injudicious use of antibiotics, and ineffective infection control and prevention measures. The rational use of antibiotics plus strict infection control are the main pillars for controlling multidrug resistant microorganisms such as MRSA in the hospital setting. These measurements should be applied nationally.